2015
DOI: 10.1021/acs.jmedchem.5b00438
|View full text |Cite
|
Sign up to set email alerts
|

6-Arylpyrazine-2-carboxamides: A New Core for Trypanosoma brucei Inhibitors

Abstract: From a whole-organism high throughput screen of approximately 87000 compounds against Trypanosoma brucei brucei, we recently identified eight new unique compounds for the treatment of human African trypanosomiasis. In an effort to understand the structure−activity relationships around these compounds, we report for the first time our results on a new class of trypanocides, the pyrazine carboxamides. Attracted by the low molecular weight (270 g•mol −1 ) of our starting hit (9) and its potency (0.49 μM), the SAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…Since the only major differences between compounds 5a , 5b , 5c , 8a and 8b are the size of secondary cyclic amino side groups and the presence of electronegative atoms other than nitrogen (oxygen and sulfur), the observed enhanced activity appeared to suggest that hydrophobicity is an important parameter. However, the introduction of bulkier amide group as exemplified by 5d leads to marked loss of activity, and these results mirror a similar trend observed by Rahmani et al …”
Section: Resultssupporting
confidence: 87%
“…Since the only major differences between compounds 5a , 5b , 5c , 8a and 8b are the size of secondary cyclic amino side groups and the presence of electronegative atoms other than nitrogen (oxygen and sulfur), the observed enhanced activity appeared to suggest that hydrophobicity is an important parameter. However, the introduction of bulkier amide group as exemplified by 5d leads to marked loss of activity, and these results mirror a similar trend observed by Rahmani et al …”
Section: Resultssupporting
confidence: 87%
“…1 H NMR (CDCl 3 , 400 MHz) δ 7. 2H,Ar),2H,Ar) 2- ethyl)isoindoline-1,3-dione (58). A mixture of 33% HBr in acetic acid (30 mL), 57 (3.4 g, 12 mmol) and DCM (50 mL) was stirred for 24 h. Water (50 mL) was added, and the mixture was extracted with EtOAc (3 × 40 mL).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Eleven hits with novel, drug-like structures and physicochemical properties were identified. We have already published the hit-to-lead optimization of five of these hits. Herein we report our work based on hit 1 (Figure ). This compound offers a very attractive starting point for hit-to-lead optimization because it exhibits good physicochemical properties, including a low molecular weight (306 g·mol –1 ), a low polar surface area (41 Å 2 ), which is necessary for CNS penetration in order to treat the second stage of HAT, and a relatively simple structure amenable to analogue synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of a high throughput screening campaign of 87000 compounds against T. b. brucei, Rahmani et al (2015) identified a new class of potential trypanocides, pyrazine carboxamides. This screening delivered a starting hit, compound 69 (EC 50 = 0.49 μM) and subsequent SAR studies were conducted concerning structural changes around the core.…”
Section: Benzamide Derivativesmentioning
confidence: 99%